1998
DOI: 10.1023/a:1005990806919
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the influence of clinical breast examination reports on the interpretation of mammograms in a breast screening program.

Abstract: The population-based Ontario Breast Screening Program (OBSP) provides two-yearly screening by both nurse examiner clinical breast examination (CBE) and two-view mammography to women aged 50 to 69. CBE alone accounts for about 5% of cancer detection. The purpose of this study was to determine whether CBE information affects radiologists' interpretation of mammography. Interpretation was defined by 1) radiologists' referral rates for diagnostic evaluation and 2) radiologists' accuracy in distinguishing cancer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The palpability alone is not an independent indicator, the diameter of the lesion correlated to the nodal state could be evaluated [37]. Knowing the result of the physical examination will not improve the diagnostic sensitivity of mammography [38], but can be crucial in the cases of mammographically occult tumors [39]. Symptomless cases usually come to the front by installation of new ancillary diagnostic methods for example scinti-mammography or MRI in screening of the population with strong family history [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The palpability alone is not an independent indicator, the diameter of the lesion correlated to the nodal state could be evaluated [37]. Knowing the result of the physical examination will not improve the diagnostic sensitivity of mammography [38], but can be crucial in the cases of mammographically occult tumors [39]. Symptomless cases usually come to the front by installation of new ancillary diagnostic methods for example scinti-mammography or MRI in screening of the population with strong family history [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…One previous study did nd such an effect to be slight, but it had no effect on the accuracy of cancer detection. 36 Other factors -for example, patient-related factors (breast volume) which could not be assessed -may affect the performance of CBE. We found that CBE plays a limited part in the early detection of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the process of interpretation such as how radiologists use clinical history in their interpretation of screening mammograms and whether this use affects accuracy. Prior research on the use of clinical history in mammography has revealed conflicting results, with two studies showing improvements in the accuracy of detection of breast cancer (12,13) and one showing no improvement (14). These prior studies were limited by small samples of radiologists (n=2–10) in some cases and use of test sets, which may not represent the use of clinical history in actual practice (1214).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on the use of clinical history in mammography has revealed conflicting results, with two studies showing improvements in the accuracy of detection of breast cancer (12,13) and one showing no improvement (14). These prior studies were limited by small samples of radiologists (n=2–10) in some cases and use of test sets, which may not represent the use of clinical history in actual practice (1214). In addition, the studies differed in the elements of the clinical history that they examined, such as patient age or results of prior clinical breast exam.…”
Section: Introductionmentioning
confidence: 99%